Umweltgeschichte und Umweltzukunft Zur gesellschaftlichen Relevanz einer jungen Disziplin Graduiertenkolleg 1024 Interdisziplinäre Umweltgeschichte - Masius, Patrick; Sparenberg, Ole; Sprenger, Jana (Universitätsverlag Göttingen, 2009)
Global climate change, the extinction of species, animal pests and natural catastrophes dominate debates on the future of the earth. Often these phenomena are considered as something new, which they are not, and many of today's discussions have their roots in the past. Therefore, to cope with our problems, forward-looking thinking has to be combined with understanding for the political, economic, social, and ecological background of our present situation. In their various contributions the authors discuss the importance of the history of ecology. The book comprises the results of a workshop on "History of Ecology and the Future of Ecology" held at the DFG Graduate College in Göttingen in July, 2008.